THE POWER OF EVIDENCE OF WITNESS TESTIMONY OBTAINED FROM CHILD VICTIMS UNDER 15 (FIFTEEN) YEARS OF AGE IN CRIME AGAINST CIVIL ACTIONS - Trisna Gamayanti Ma’na (CV. RADJA PUBLIKA, 2025)
One of the pieces of evidence in criminal cases is testimony based on things heard, seen and experienced by the witness directly related to the crime that occurred. Testimony is given by a person who is legally considered an adult and meets the qualifications as a valid witness as regulated in Law Number 8 of 1981. This condition does not cause obstacles in the process of proving a crime, but sometimes a crime or criminal event is only witnessed by a child, especially if the child is under 15 (fifteen years old) who is the victim of the crime. If we look at the provisions contained in Article 171 letter (a) of Law Number 8 of 1981, a child who witnesses by seeing, hearing and/or experiencing the crime himself by stating the reasons based on their knowledge can give testimony without being sworn in. Therefore, it is permitted to obtain information from child witnesses. However, the position of witness information obtained from child victims of crimes against morality which is basically not sworn in could result in the defendant of the crime against morality arguing in court that the crime allegedly committed by the defendant was done on the basis of mutual consent and not by coercion. This certainly needs to be carefully examined by the judge in the process of proof in order to assess the evidence as a consideration for the judge in sentencing decision. When resolving a case, it is necessary to pay attention to the evidence against child witnesses in the criminal justice process, this situation will make the child again face the perpetrator who does not rule out the possibility of suppressing the child's psyche and will affect the child's psychology and also especially the child's testimony in court which in the end the child's testimony will influence the judge's considerations when making a decision on the case. Based on the description above, it can be concluded that although the evidence in the form of witness statements obtained from child victims of crimes against morality can be heard in court, to determine the evidentiary strength of the evidence, it is necessary to examine the position of the child witness's statement as evidence in court as stipulated in statutory regulations.